Sistem Informasi Geografis Pemetaan Mitra Menggunakan Google Maps API dan Framework Laravel - Herdiesel Santoso; Zilfana Falahi; Ahmad Arif Nurrahman; Harimanto (PPPM Institut Teknologi Pagar Alam, 2023)
PT Mustaka Multi Tehnik is a company engaged in several business units, including inthe field of producing mosque domes with several types of domes such as stainless steel,decorative colors, color panels and color enamel. PT Mustaka Multi Tehnik mosque domeproducts have been used by tens of thousands of mosques and prayer rooms spread throughoutIndonesia. Marketing PT Mustaka Multi Tehnik has not been able to see the distribution ofpartners in the form of a digital visualization map. Therefore, it is necessary to have a system thatrecords data in the form of a digital visualization map to display the potential of partners tofacilitate marketing. The geographic information system is built by the Waterfall model SystemDevelopment Life Cycle (SDLC) development method. Unified Modelling Language (UML) asa tool for documenting and specifying the system. Expected outputs are implemented from theLaravel framework and Google Maps APIs to translate latitude and longitude data into objects.After the system is successfully built, the next stage is to carry out functional testing of the blackbox method. With this web-based geographic information system, recording partner data andpotential partner data can already be done digitally. The system successfully runs functionally forusers because of the black box method testing, the test also avoids bugs and errors in the system